2011
DOI: 10.1103/physrevb.84.144414
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast magnetization dynamics rates within the Landau-Lifshitz-Bloch model

Abstract: The ultra-fast magnetisation relaxation rates during the laser-induced magnetisation process are analyzed in terms of the Landau-Lifshitz-Bloch (LLB) equation for different values of spin S. The LLB equation is equivalent in the limit S → ∞ to the atomistic Landau-Lifshitz-Gilbert (LLG) Langevin dynamics and for S = 1/2 to the M3TM model [B. Koopmans, et al. Nature Mat. 9 (2010) 259]. Within the LLB model the ultra-fast demagnetisation time (τ M ) and the transverse damping (α ⊥ ) are parameterized by the intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 61 publications
7
100
0
Order By: Relevance
“…It was shown that the M3TM and LLB models are equal in the description of the heat-triggered, longitudinal spin-dynamics. 130 In certain limits, both can be solved analytically, and novel scenarios can be developed within these frameworks.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…It was shown that the M3TM and LLB models are equal in the description of the heat-triggered, longitudinal spin-dynamics. 130 In certain limits, both can be solved analytically, and novel scenarios can be developed within these frameworks.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Within the LLB model a similar estimate can been found. 13 In particular, for ferromagnets, the relaxation time has been shown to be defined as τ ∼ χ (T )/λ, where χ = (∂m/∂H) H→∞ is the longitudinal susceptibility and m is the thermally averaged spin polarization. This depends on: (i) the particular dissipation mechanism represented by the coupling parameter λ, and (ii) the longitudinal susceptibility χ (T ).…”
Section: Estimation Of the Temperature Dependent Magnetization Relmentioning
confidence: 99%
“…13,[37][38][39][40][41][42] In ferrimagnets, there is a large interest on demagnetization rates of each species, following the use of X-ray magnetic circular dichroism 5 to monitor the sub-picosecond dynamics of each sublattice magnetization individually. 4 Thermal effects dominate the magnetization dynamics during the heating produced by the laser.…”
Section: Estimation Of the Temperature Dependent Magnetization Relmentioning
confidence: 99%
See 2 more Smart Citations